Profile and correlates of injecting-related injuries and diseases among people who inject drugs in Australia. (1st November 2020) - Colledge, Samantha; Larney, Sarah; Bruno, Raimondo; Gibbs, Daisy; Degenhardt, Louisa; Yuen, Wing See; Dietze, Paul; Peacock, Amy
Highlights: One-third of participants reported any IRID in the past month. 16 % of the sample reported two or more IRID in the past month. Thrombophlebitis distinguished a more complex IRID profile. Re-using needles was associated with more severe IRID presentations. Abstract: Introduction: People who inject drugs (PWID) commonly experience harms related to their injecting, many of which are consequences of modifiable drug use practices. There is currently a gap in our understanding of how certain injecting-related injuries and diseases (IRID) cluster together, and socio-demographic and drug use characteristics associated with more complex clinical profiles. Method: Surveys were conducted with 902 Australian PWID in 2019. Participants provided information regarding their drug use, and past month experience of the following IRID: artery injection, nerve damage, skin and soft tissue infection, thrombophlebitis, deep vein thrombosis, endocarditis, septic arthritis, osteomyelitis, and septicaemia. We performed a latent class analysis, grouping participants based on reported IRID and ran a class-weighted regression analysis to determine variables associated with class-membership. Results: One-third (34 %) of the sample reported any IRID. A 3-class model identified: 1) no IRID (73 %), moderate IRID (21 %), and 3) high IRID (6%) clusters. Re-using one`s own needles was associated with belonging to the high IRID versus moderate IRID class (ARRR = 2.38; 95 % CI = 1.04−5.48). Other factors, including daily injecting and past 6-month mental health problems were associated with belonging to moderate and high IRID classes versus no IRID class. Conclusion: A meaningful proportion of PWID reported highly complex IRID presentations distinguished by the presence of thrombophlebitis and associated with greater re-use of needles. Increasing needle and syringe coverage remains critical in addressing the harms associated with injecting drug use and expanding the capacity of low-threshold services to address less severe presentations might aid in reducing IRID amongst PWID.